Analysis of the impact of the Work From Home Policy on Changes in Stock Prices and Transaction Volume Study of Telecommunications Companies at IDX - Arie Setyo Dwi Purnomo (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2020)
The work from home policy due to the COVID 19 pandemic is an alternative in preventing the spread of the COVID 19 virus. The general public must get used to working and learning by utilizing telecommunications networks to support work. The increase in internet network traffic is expected to provide a stimulus for telecommunications companies. This study examines the sentiment of work from home to changes in price and transaction volume of shares of two companies, namely PT. Telkom Indonesia Tbk and PT. XL Axiata. Tbk. The analysis technique in this study uses quantitative analysis techniques with a paired t-test sample test. Data collected from the Indonesia Stock Exchange with the type of secondary data. Researchers used the paired t-test sample test using SPSS 21 software. The results showed that PT Telkom Indonesia Tbk indicated a significant price change of Rp. 343 before the policy but the volume of transactions increased after the announcement of the work from home policy. PT XL Axiata Tbk had a significant change of Rp. 126 which was higher before the work from home policy, but the transaction volume had no significant effect before and after the work from home policy.